An Assessment on Destination Characteristics: The Case Study of Pulau Perhentian - Muhibudin, Masitah; Mohamed, Badaruddin (EDP Sciences, 2014)
The growth of tourism in the small island has brought both positive and negative impacts towards the environment particularly. However, the growth seems disregard with the limited natural resources, facilities, accessibilities and others. Pulau Perhentian, one of the well known islands in Malaysia that is struggling with many physical carrying capacity related issues such as waste management, supply of accommodation, utilities, facilities and environmental protection. Consequently, this study aims to evaluate the destination characteristics that contribute to the management of physical carrying capacity using the criteria matrix. Finding shows that the physical development has marked the island into a yellow colour that indicates the condition of current development. This evaluation is hoped to contribute and assist in future tourism activities and physical developments in Perhentian.